A Review of Micro Hydro Power Plant (MHPP) as a Solution to Reach Remote Areas of Electricity (UNIB Press, 2023)
A micro hydro power plant (MHPP) is a small-scale power plant that converts the potential energy of the air into mechanical work, turning turbines and generators to generate electrical power. Small scale, which is around 0-100 kW. The construction of a Micro-hydro Power Plant (MHPP) is an alternative supply of electrical energy, especially in rural areas that are not covered by the electricity grid State Power Plant. MHPP has a high potential as an alternative to renewable energy sources. Thus, the reliability of the system built is a must forget quality electricity. In a power plant, what is considered is the stability of the output voltage generated by the generator; this is necessary to keep the consumer's equipment from being damaged. Unstable voltage can also Age-reduce equipment (lifetime) owned by consumers. Keywords: Micro Hydro Power Plant 2; Alternative, 3; Electric Power